2010
DOI: 10.1053/j.gastro.2010.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Reduces Acute Ethanol-Induced Hepatotoxicity and Steatosis in Mice

Abstract: Background & Aims Alcohol abuse is a major cause of liver injury. The pathologic features of alcoholic liver disease develop over prolonged periods, yet the cellular defense mechanisms against the detrimental effects of alcohol are not well understood. We investigated whether macroautophagy, an evolutionarily conserved cellular mechanism that is commonly activated in response to stress, could protect liver cells from ethanol toxicity. Methods Mice were acutely given ethanol by gavage. The effects of ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
545
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 450 publications
(584 citation statements)
references
References 28 publications
34
545
2
3
Order By: Relevance
“…On the one hand, autophagy has been shown to protect against liver injury from alcohol and oxidative stress. 26,27 On the other, autophagy contributes to activation of HSC, a key process leading to hepatic fibrosis in HSC. 28 In our system, activation of GCN by histidine deprivation failed to induce autophagy in HSC and had a protective effect, counteracting the loss of viability caused by autophagy inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, autophagy has been shown to protect against liver injury from alcohol and oxidative stress. 26,27 On the other, autophagy contributes to activation of HSC, a key process leading to hepatic fibrosis in HSC. 28 In our system, activation of GCN by histidine deprivation failed to induce autophagy in HSC and had a protective effect, counteracting the loss of viability caused by autophagy inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that a decline in autophagy of mitochondria (mitophagy) could be contributing to the increased mitochondria number caused by intragastric alcohol feeding. With acute alcohol feeding, mitophagy seems to increase in the liver (45). However, the impact of chronic alcohol feeding on the clearance of mitochondria remains to be determined.…”
Section: Increased Mitochondrial Respiration and Increased Componentsmentioning
confidence: 99%
“…74 Autophagy has been shown to protect against ethanol-induced fatty liver injury. 75 Autophagy was found to be increased both in the livers of binge alcohol-fed mice and cultured hepatocytes treated with ethanol. Autophagic degradation of long-lived proteins was not increased, but findings of increased numbers of autophagosomes containing LDs and mitochondria suggested that selective increases in lipophagy and mitophagy occurred in response to alcohol.…”
Section: Lipophagy Mediates Resistance To Cell Deathmentioning
confidence: 99%